The Role of the Madrasah Principal in Fostering Ideal Leadership at MAN 4 Banyuwangi - Nico Prasetiyo; Akun Fariha Imaroh; Ainur Rofiq (DAAR EL-IDARAH: Journal of Islamic Education Management, 2026)
This study aims to comprehensively analyze the strategic role of the madrasah principal in establishing an ideal Islamic educational leadership model at MAN 4 Banyuwangi. Employing a qualitative approach with an explanatory case study design, data were gathered from six key informants—comprising the madrasah principal, vice-principals of curriculum, student affairs, and public relations, as well as educational support staff—through in-depth interviews, passive participant observation, and documentary studies. Data trustworthiness was ensured using source and technique triangulation, while data analysis applied the interactive analysis model of Miles, Huberman, and Saldaña continuously. The findings reveal that the ideal leadership at MAN 4 Banyuwangi is realized through the tactical integration of Islamic prophetic values (amanah, 'adl, shura, and uswah) with modern transformational-participative leadership styles. The principal successfully transformed traditional administrative-bureaucratic functions into those of an inclusive change leader by actively involving teachers in strategic policy formulation. Furthermore, the principal’s interpersonal approach and exemplary behavior (uswah) proved effective as a catalyst for educators' intrinsic motivation, navigating the financial rigidities imposed by state budget allocation (DIPA) regulations. The internalization of these spiritual values has significant implications for cultivating a solid, religious, and quality-driven organizational culture that is adaptive to the socio-cultural challenges of a society in transition. This research offers a theoretical contribution to constructing a contemporary value-based leadership model within Islamic educational institutions.